Lycopene and ellagic acid prevent testicular apoptosis induced by cisplatin - Türk, G; Çeribaşı, Ao; Şahna, E; Ateşşahin, A (My University, 2011)
The aim of this studywasto investigate the possible protective effects of lycopene (LC) and ellagic acid (EA) on cisplatin (CP)-induced testicular apoptosis in male rats. The control group was treated with placebo; LC, EA and CP groups were given alone LC, EA and CP, respectively; the CP + LC group was treated with a combination of CP and LC; and the CP + EAgroup was treated with a combination of CP and EA. Although CP significantly increased the number of Bax-positive (apoptotic) cells it had no effect on the number of Bcl- 2-positive (antiapoptotic) cells compared with the control group. Administration of CP caused significant increase in lipid peroxidation and nonsignificant decrease in superoxide dismutase (SOD) activity along with some histopathological lesions in testicular tissue. However, combined treatments of LC or EA in addition to CP tended to prevent the CP-induced testicular apoptosis, histopathological lesions and lipid peroxidation.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cisplatin Lycopene Ellagic acid Apoptosis Lipid peroxidation Testis